Effects of Arbuscular Mycorrhizal Fungi on Alleviating Cadmium Stress in Medicago truncatula Gaertn - Wanting Li; Ke Chen; Qiong Li; Yunlai Tang; Yuying Jiang; Yu Su (Plants, 2023)
Heavy metal contamination is a global problem for ecosystems and human health. Remediation of contaminated soils has received much attention in the last decade. Aided mitigation of heavy metal phytotoxicity by arbuscular mycorrhizal fungi (AMF) is a cost-effective and environmentally friendly strategy. This study was carried out to investigate the mitigation effect of AMF inoculation on heavy metal toxicity in Medicago truncatula under soil cadmium stress. Therefore, a pot experiment was designed to evaluate the growth, chlorophyll fluorescence, Cd uptake and distribution, malondialdehyde (MDA) content, root soil physicochemical properties, and metabolite profile analysis of M. truncatula with/without AMF inoculation in Cd (20 mg/Kg)-contaminated soil. The results showed that inoculating AMF under Cd stress might enhance photosynthetic efficiency, increase plant biomass, decrease Cd and MDA content, and improve soil physicochemical properties in M. truncatula. Non-targeted metabolite analysis revealed that inoculation with AMF under Cd stress significantly upregulated the production of various amino acids in inter-root metabolism and increase organic acid and phytohormone synthesis. This study provides information on the physiological responses of mycorrhizal plants to heavy metal stress, which could help provide deeper insight into the mechanisms of heavy metal remediation by AMF.